Підвищення ефективності роботи газоочистного обладнання в агломераційному виробництві - Кащеєв, М. А.; Владі, В. О.; Руденко, М. Р. (Physico-technological Institute of Metals and Alloys, 2023)
The analysis of recent studies and publications on the use of equipment for cleaning of sinter gases is carried out; these are battery multicyclones and electrocyclones, bag filters, electrostatic precipitators. It is established that when using such devices for cleaning of sinter gases, there are significant problems and shortcomings associated with the treatment of a large number of highly dusty gases. These are low efficiency due to the accumulation of dust in the equipment elements, the large size of the filters, rapid wear of the elements of the used devices, high aerodynamic resistance, increased operating costs, etc. Based on the analysis of shortcomings of existing equipment, the authors of the article performed computer simulation of the movement of dusty gas flows through a dust deposition and established the dependence of the speed, direction of gas flow, size of dust and the efficiency of the inertial device, depending on its resistance. The VAV-250-AFK inertial deposition apparatus for preliminary gas purification was developed and tested on sinter machine No. 12 of the sinter plant of PJSC "Dnieper metallurgical plant". According to the results of measurements conducted by the environmental service of the plant, the dust content of gases at the outlet of the apparatus is 0.92 g/nm3 when the incoming dust is 3 g/nm3. Cleaning efficiency was about 70 %. A design and technical solution is proposed for replacing battery cyclones with the device of thin gas purification "VAV400/50D", that will allow us to achieve European standards on dust emission in the atmosphere up to 40–50 mg/nm3. A technical solution to reduce gas dust during the implementation of our developments for various conditions of equipment location is possible. Three options are proposed for the modernization of existing treatment equipment in order to increase its efficiency. When introducing the proposed technical solutions, it is possible to obtain a steady reduction in the content of dust and harmful gases in the outgoing sintering gases to established standards and to solve the dust problem of industrial cities with a working sintering industry, which are the main sources of dust and harmful gas emissions from the metallurgical enterprise.